Preventable Complications and Deaths after Emergency Nontrauma Surgery. Issue 9 (September 2018) - Linnebur, Megan; Inaba, Kenji; Chouliaras, Konstantinos; Low, Garren M.I.; Mansfield, Nicole; Benjamin, Elizabeth R.; Lam, Lydia; Demetriades, Demetrios
The objective of this study was to investigate the frequency and cause of preventable and potentially preventable complications on an emergency nontrauma surgical service. The study is a retrospective review conducted at an academic teaching hospital. All patients were assessed (January 2010–June 2012) for emergency general surgical conditions, excluding trauma. The main outcome measures were preventable and potentially preventable complications and deaths, treatments, loop closure mechanisms, and impact on outcomes. The results showed that of 9078 nontrauma emergency surgical admissions and consultations, 194 patients (2.1%) had 261 complications. One hundred and ten (42.1% of total complications) were preventable. The most common causes of preventable complications were delay in management or diagnosis (n = 45, 41% of all preventable complications), technical/iatrogenic (n = 28, 25%), and infectious (n = 18, 16%). The most common nonpreventable complication was infectious (n = 84, 82% of all complications). The most common diagnoses associated with preventable complications were acute cholecystitis (n = 27, 25%), acute appendicitis (n = 25, 23%), and small bowel obstruction (n = 7, 6%). Preventable complications changed management in 80 per cent of cases. Of three (0.01%) mortalities, two were preventable. The mortality rate in emergency nontrauma surgery is low. A significant burden of complications remains. A large proportion are preventable or potentially preventable, with many changing management. These preventable errors are important targets for quality improvement efforts as the specialty of acute care surgery evolves.